2006
DOI: 10.1111/j.1365-2362.2006.01712.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and endothelial markers in women with polycystic ovary syndrome

Abstract: Background  Women with polycystic ovary syndrome (PCOS) carry a pattern of cardiovascular risk factors. Endothelial dysfunction and chronic inflammation are early findings in the atherosclerotic process. The purpose of the study was to investigate the coexistence of active inflammation markers and endothelial dysfunction in young women with PCOS, and their relationship with metabolic and hormonal abnormalities of the syndrome. Materials and methods  Twenty‐five young women with PCOS and 25 controls of similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
111
2
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(133 citation statements)
references
References 56 publications
10
111
2
10
Order By: Relevance
“…Consistent with our results, most of the studies, but not all [8,12], demonstrated impaired endothelial function in PCOS using either noninvasive endothelium-dependent (FMD) and-independent (glyceroltrinitrate, GTN) changes in the brachial artery or invasive methodology [4,6,10,11,24] compared with the controls. Among several circulating endothelium-derived vasoactive molecules, ET-1 is considered one of the best indices of abnormal vascular reactivity, playing an important role in the early events of endothelial dysfunction [4].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Consistent with our results, most of the studies, but not all [8,12], demonstrated impaired endothelial function in PCOS using either noninvasive endothelium-dependent (FMD) and-independent (glyceroltrinitrate, GTN) changes in the brachial artery or invasive methodology [4,6,10,11,24] compared with the controls. Among several circulating endothelium-derived vasoactive molecules, ET-1 is considered one of the best indices of abnormal vascular reactivity, playing an important role in the early events of endothelial dysfunction [4].…”
Section: Discussionsupporting
confidence: 90%
“…Among several circulating endothelium-derived vasoactive molecules, ET-1 is considered one of the best indices of abnormal vascular reactivity, playing an important role in the early events of endothelial dysfunction [4]. With regard to ET-1 levels, we confirm the other authors' results on increased levels of ET-1 in PCOS women [3,4,9,10]. Furthermore, impaired vascular reactivity and increased level of ET-1 were linked to markers of hyperandrogenism (TT, FAI).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Human experiments have shown microvascular dysfunction in PCOS, as indicated by the inhibition of Ach-dependent vasodilation (5). Endothelial dysfunction and damage has been shown to be enhanced by increased inflammatory and soluble activation markers (24). Paraoxonase-1 and flow-mediated dilation have been shown to be useful predictors of endothelial dysfunction (25).…”
Section: Sara Vascular Insulin Resistance In Pcos Fertil Steril 2012mentioning
confidence: 99%